ANALISIS PUTUSAN LEPAS DARI SEGALA TUNTUTAN PADA TINDAK PIDANA PENGANIAYAAN (StudiPutusanNomor 1002/Pid.B/2008/PN.Smg) - Okerius Sisokhi (Jurnal Panah Hukum, 2022)
Decision analysis is a problem solving process (case) that starts with a hypothesis (allegation, etc.) by seeking the truth through observation, experimentation, and so on. A verdict Abandoned from all charges is a lawsuit for the actions committed by the defendant at the indictment of the public prosecutor, but cannot be sentenced, because the act is not a crime. The crime of maltreatment is an act that is intentionally carried out on the body which causes pain or injury and even death. The type of research used is normative legal research, with a problem approach method through statutory regulations, case approaches, and analytical approaches. Data collection was carried out using secondary data obtained through library materials consisting of primary legal materials and secondary legal materials. The data analysis used was qualitative analysis and drawing conclusions using the deductive method. Based on the research findings and discussion, it can be concluded that the Panel of Judges in passing their decision released all charges for the crime of persecution (study of decision number 1002/Pid.B/2008/PN .Smg) is inappropriate because the perpetrator's actions are pure criminal acts and do not fulfill the elements of forced defense (noodweer) as stipulated in Article 49 paragraph (1) of the Criminal Code, namely that there is an attack that is against the law, there is an instant attack and the defense made is necessary . The judge's consideration in decision number 1002/Pid.B./2008/PN.Smg is a juridical consideration, that is, the perpetrator's actions have violated the provisions of Article 351 paragraph (3) in conjunction with Article 55 of the Criminal Code, and have fulfilled the evidentiary requirements in the trial referred to in Article 183 of the Criminal Procedure Code. , and non-juridical considerations where the perpetrator has never been punished before, and the perpetrator admits his actions. The author suggests that the panel of judges evaluate and consider the facts revealed in the trial process in terms of examining evidence, namely witness statements, statements of the accused and evidence submitted by the public prosecutor and that the panel of judges impose criminal penalties on the perpetrators